Role of Dectin-1 receptor on cytokine production by human monocytes challenged with Paracoccidioides brasiliensis - Romagnolo, Alexandre Giannecchini [UNESP]; de Quaglia e Silva, Juliana Carvalho [UNESP]; Della Coletta, Amanda Manoel [UNESP]; Gardizani, Taiane Priscila [UNESP]; Martins, Ana Teresa Loyola [UNESP]; Romagnoli, Graziela Gorete [UNESP]; Kaneno, Ramon [UNESP]; de Campos Soares, Angela Maria Victoriano [UNESP]; De Faveri, Julio [UNESP]; Dias-Melicio, Luciane Alarcão [UNESP] (Wiley, 2018)
Fungal recognition by Dectin-1 receptor triggers a series of cellular mechanisms involved in a protective activation of the immune system. In this study, we aimed to evaluate the participation of Dectin-1 receptor in the induction of IL-8, TNF-α, IL-12, IL-10 and IL-17A secretion by human monocytes activated with different cytokines, and challenged in vitro with Paracoccidioides brasiliensis (P. brasiliensis). Our results show that monocytes challenged with P. brasiliensis (Pb265) are able to produce IL-12, IL-8, IL-17, IL-10 and TNF-α. Dectin-1 receptor blockage decreased the IL-12, IL-17, IL-10 and TNF-α levels indicating the participation of such receptor in the induction of these cytokines. Only IL-8 production was not affected by the blockage. Cells activation with different cytokines showed that GM-CSF was able to induce secretion of all cytokines and the receptor blockage prior to the challenge also decreased the cytokine secretion, except IL-8. Monocytes activated with TNF-α promoted IL-8, IL-10 and TNF-α production, whereas stimulation with IFN-γ promoted mainly IL-12 and TNF-α. Thus, these findings bring new and important knowledge about Dectin-1 participation in cytokines production by monocytes challenged with Pb265.
Keywords: cytokines; Dectin-1 receptor; monocytes; Paracoccidioides brasiliensis